Influence of cultural factors on choice of childbirth place among women in Oyigbo Local Government Area, Rivers State, Nigeria - Ngozi Afulenu Obika-Ndiri; Chizoma Millicent Ndikom; Ogochukwu Immaculate Obika; Omineokuma Tubonemi Aseminaso (Wolters Kluwer Medknow Publications, 2023)
Objectives: This study aims to ascertain if cultural factors influence the childbirth place choice of women in Oyigbo. Materials and Methods: The study used a cross-sectional study design using a self-structured questionnaire as the instrument to collect data from 384 volunteers through simple random sampling, and these data were analyzed using frequency and percentage for descriptive statistics while Chi-square was used for inferential statistics at 0.05 level of significance. Results: The influence of cultural factors such as family traditions (χ2 = 12.56, P = 0.006), beliefs (χ2 = 70.66, P = 0.000), lack of confidence in health facilities (χ2 = 367.83, P = 0.000), and the presence of male skilled birth attendants (χ2 = 50.85, P = 0.000) were statistically significant to the choice of childbirth place, while patriarchal system (χ2 = 2.99, P = 0.393) was not statistically significant to the choices of childbirth places of women in Oyigbo. Religion had a statistically significant influence on childbirth place (χ2 = 125.46, P = 0.000). Conclusion: This study shows that religious and cultural factors have a significant influence on the childbirth place choices of women in Oyigbo Local Government Area of Rivers State.